MENGGAPAI TENAGA TERAMPIL MENGELOLA DANA DESA DI SMK PGRI 2 CIBINONG BOGOR - Edy Sudaryanto (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This study aims to identify and analyze opportunities, challenges, constraints and efforts of vocational high school or Sekolah Menengah Kejuruan (SMK) to create graduates especially accounting programs that are able to manage village funds. The object of the study are accounting program students of SMK PGRI 2 Cibinong. Data used in this study are primary data and secondary data. Data is collected using interviews, observation, and documentation. Data analysis methods use data reduction, data display and conclusion drawing/verification. The results of this study show that the SMK PGRI 2 Cibinong Bogor aware of the opportunities for SMK graduates of the accounting program to fill the scarcity of skilled human resources to manage village funds. But teachers have less experience in the practice of village fund accounting so that they do not have confidence in  teaching. Other constraints are less discussion of government accounting in the accounting syllabus and the absence of a standard handbook/module for teachers to teach accounting subjects.